Behavioral problems in adolescents raised by their grandparents - Bernedo, Isabel Mª; Fuentes, María Jesús; Fernández, Milagros (The Spanish Journal of Psychology, 2008)
This research analyzes, for the first time using a Spanish sample, the behavioral problems of adolescents in the custody of their grandparents. The sample consisted of 68 adolescents (31 boys and 37 girls, with a mean age of 13.7 years) in the custody of 54 grandparents with an average age of 65.9 years for the grandfathers, and 63.6 years for the grandmothers. The instrument employed was the Child Behavior Checklist (CBCL;; Achenbach, 2001). The results indicate that the majority of both boys and girls can be classified within the normal range on scales of internal behavior, external behaviour and total behavioral problems. When gender and age differences were analyzed, it was found that boys had more behavioral problems than girls on scales of incompliance with rules and external behavior. Meanwhile, it was shown that older adolescents had more somatic problems, as well as more behavioral problems, as measured by both the internal scale and total scale of the CBCL, than the younger participants.